2000
DOI: 10.1149/1.1393554
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Materials as a Ceramic Filler in Solid Composite Polyethylene Oxide-Based Electrolytes

Abstract: cation and the spontaneous polarization of the ferroelectric ceramics. Also, the interfacial stability between ferroelectric ceramics added to composite polymer electrolytes and a lithium metal electrode is reported and discussed in terms of applications for lithium batteries. ExperimentalAll the polymer electrolytes described here were prepared by the solvent-casting technique using tetrahydrofuran (THF) as a carrier solvent. High-molecular-weight (Mw ϭ 6 ϫ 10 5 g/mol) PEO (Aldrich Chemical) and Li salts [LiC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(120 citation statements)
references
References 21 publications
1
117
1
1
Order By: Relevance
“…5),12), 13) In this study, we used mesoporous silica (MPS)/Li + conductive PEO (Li-PEO) hybrid electrolytes in lithium polymer batteries to improve the mechanical strength of the SPE. MPS is composed of stacked SiO 2 channels arranged in a hexagonal array with pore sizes ranging from 2 to 10 nm.…”
Section: )6)mentioning
confidence: 99%
“…5),12), 13) In this study, we used mesoporous silica (MPS)/Li + conductive PEO (Li-PEO) hybrid electrolytes in lithium polymer batteries to improve the mechanical strength of the SPE. MPS is composed of stacked SiO 2 channels arranged in a hexagonal array with pore sizes ranging from 2 to 10 nm.…”
Section: )6)mentioning
confidence: 99%
“…We also found that the addition of nanosize BaTiO 3 (0.1 µm) was effective to reduce the interface resistance between lithium metal and PEO 10 LiTFSI. 19,20 The interface resistance between lithium metal and PEO 10 LiTFSI (ca. 25 ³ cm 2 ) was constant for 10 days at 80°C.…”
Section: Electrode Performance Of the Wslementioning
confidence: 99%
“…Shin et al reported interesting results for a PEO-based polymer electrolyte with ionic liquids. 33,34 A composite polymer electrolyte of PEO 20 LiTFSI and N-butyl-N-methylpyrrolidum-TFSI exhibited high electrical conductivity at a moderate temperature and good stability with lithium metal. The addition of RTIL into the polymer electrolyte results in enhancement of the electrical conductivity.…”
Section: ¹2mentioning
confidence: 99%
“…The addition of polymer to salt solution increases the viscosity, which is generally accompanied by a small decrease in conductivity [12]. In solvent free polymer electrolytes, the addition of micron size inorganic fillers such as fumed silica, zeolite, Al 2 O 3 , TiO 2 , etc., has been reported to result in an improvement in the electrode-electrolyte interfacial stability, conductivity along with an improvement in mechanical properties of electrolytes [13][14][15][16]. The aim of the present work is to study the effect of nano size fumed silica on the properties of polymer gel electrolytes.…”
Section: Introductionmentioning
confidence: 99%